Improving the Numeracy Skills Elementary School Students by Problem Based Learning Model - Pudjastuti, Komang Tri; Agustika, Gustri Ngurah Sastra; Wiyasa, I Komang Ngurah (Universitas Pendidikan Ganesha, 2024)
There are four categories of 21st century skills that are urgently needed nowadays: Personal Skills, Social Skills, Information and Knowledge and Digital Literacy. However, the literacy and numeracy skills of elementary school students are still in the low category. This research aims to analyze the significant influence of the Problem Based Learning model on the numeracy abilities of fifth grade elementary school students. This research is a quasi-experimental with a non-equivalent control group design. The research population involved 118 students. Samples were taken using a cluster random sampling technique and the experimental group sample was 26 students and the control group sample was 19 students. The data collection method uses the test method, with the type of test used being a multiple choice test consisting of 20 questions. Based on the results of data analysis, the post-test score analysis results in the experimental group were 82.31 and were in the high category, while the post-test score analysis results in the control group were 63.68 and were in the low category. The results of the t-test analysis show that tcount (10.038) is greater than t¬ (2.016), so H0 is rejected and H1 is accepted. It was concluded that there was a significant influence of the Problem Based Learning learning model on the numeracy abilities of fifth grade elementary school students.